The perfect family - Harding, Robyn (Gallery Books, 2021)
"A sharp, smart, and compulsively readable new novel from the #1 international bestselling author of The Party about a picture-perfect family--all hiding dark secrets--whose lives are upended by a dangerously escalating series of pranks"--